Pengaruh Desain Pekerjaan dan Pengembangan Karir terhadap Prestasi Kerja Melalui Kepuasan Kerja Sebagai Variabel Intervening - Wahyudi, Fitria Desy; Suryatni, Mukmin (Postgraduate, University of Mataram, 2024)
This study aims to analyze the effect of job design and carrer development on work performance with job satisfaction as a variable that intervenes on traffic unit personnel of the east lombok district police. The method of using data using a questionnaire. Population of 59 personnel, with a sample as much 59. The analytical method uses Structural Equation Modeling (SEM) using the SmartPLS v.4.0 tool. The results showed that first, design has a positive but not significant effect on work performance. Second, the career development has a positive and significant effect on work performance. Third, job design has a positive and significant effect on job satisfaction. Fourth, the career development has a positive effect on job satisfaction. Fifth, job satisfaction has a positive and significant effect on work performance. Sixth, job design has a positive and significant effect on work performance through job satisfaction. Seventh, the career development has a positive and significant effect on employee performance through job satisfaction. Research results can be used as a basis for improving and improving job design, career development, job satisfaction, and work performance.